Expression and localization of tight junction-related proteins in adult rat pituitary stem/progenitor cell niches - Saishu YOSHIDA; Hideaki YURINO; Masaaki KOBAYASHI; Naoto NISHIMURA; Kentaro YANO; Ken FUJIWARA; Shin-ichi HASHIMOTO; Takako KATO; Yukio KATO (The Society for Reproduction and Development, 2022)
Pituitary endocrine cells are supplied by Sox2-expressing stem/progenitor cells in the anterior lobe of the adult pituitary gland. These SOX2-positive cells are maintained in two types of microenvironments (niches): the marginal cell layer (MCL)-niche and the parenchymal-niche. Recently, we isolated dense SOX2-positive cell clusters from the parenchymal-niche by taking advantage of their resistance to protease treatment as parenchymal stem/progenitor cell (PS)-clusters. In the present study, by analyzing these isolated PS-clusters, we attempted to identify novel structural characteristics of pituitary stem/progenitor cell niches. Quantitative real-time PCR showed that tight junction-related genes were distinctly expressed in the isolated PS-clusters. Immunocytostaining showed that the tight junction molecules, ZO-1 and occludin, were localized in the apical membrane facing the pseudo-follicle-like structure of the isolated PS-clusters regardless of the expression of S100β, which distinguishes the sub-population of SOX2-positive cells. Furthermore, immunohistochemistry of the pituitary glands of adult rats clearly demonstrated that ZO-1 and occludin were densely present in the parenchymal-niche encircling the pseudo-follicle, while they were observed in the apical membrane in the MCL-niche facing the residual lumen. Collectively, these tight junction-related proteins might be involved in the architecture and maintenance of the plasticity of pituitary stem/progenitor cell niches.